ANALISIS PEMANFAATAN BEASISWA BIDIKMISI DALAM MENUNJANG PRESTASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Siti Sa’diah Irawaty; Sri Kartikowati; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to determine the utilization of Bidikmisi scholarship to support students’ learning achievement. The subject of this study is students the study Program of Economics Education, Faculty of Teacher Training and Education, Riau University. Data were obtained from 23 students scholarship recipients 2016, 2017, and 2018. The data collection techniques used is interview. Technical analysis of data used is qualitative descriptive. Researchers grouped 3 categories of IPK namely high value IPK, moderate value IPK and low value IPK as the basis of determination based on students’ learning achievement. The results showed that from eight indicators, to determine the utilization of Bidikmisi scholarship Program for Students of Economics Education, is separated into 2, namely academic and non-academic benefits. Academic benefits consisting 5 indicators, namely 1) Buy a college book, 2) Pay Tuition fee, 3) Photocopy of coursework, 4) coursework, electronics and pulse package 5) fulfillment of daily necessities, they utilize Scholarship Fund. While the non-academic benefits consist of 3 indicator, namely 6) fulfillment of lifestyle, 7) body care, and 8) transportation, they do not utilize the Bidikmisi scholarship fund.Key Words: Utilization Of Bidikmisi Scholarship, Learning Achievement